Peran Solidaritas Pada Pada Masyarakat Multikultural Dalam Proses Perdagangan di Wilayah Gunung Pangilun Kota Padang - Irwan Irwan; Zusmelia Zusmelia; Felia Siska; Intan Putri Rusvita; Nadila Febrina Eka Putri; Yenni Melia; Nur Inayati Saiful (Universitas Muhammadiyah Makassar, 2023)
Social solidarity shows a sense of solidarity that pays attention to a situation in individual or group relationships based on shared moral feelings and beliefs. The purpose of this study was to analyze the role of solidarity in a multicultural society for street vendors in the Gunung Pangilun area, Padang city. This study uses a qualitative approach by observing objects. The method of data collection was observation and interviews with several street vendors in the Gunung Pangilun area. The results of this stidy indicate that the solidarity of street vendors on Gunung Pangilun can be seen when they interact, they still maintain friendships even though they are both competing in selling their wares. The way they help each other in selling, such as exchanging money to return buyers’ money and having mutual trust in one another.